Mössbauer spectroscopic study of the forms of iron in normal human liver and spleen tissue - W. Chua-anusorn (2018)
Mössbauer spectra of 12 normal human spleen and 12 normal human liver samples (post mortem) from Australia and Thailand have been recorded at 78 K. The spectra show the presence of iron in the form of ferrihydrite, together with some deoxyhemoglobin and methemoglobin in some samples. The spectra were used in conjunction with elemental analysis to calculate the non-heme iron concentrations in the tissues. The mean non-heme iron concentration in the Thai livers was significantly less than that for the Australian samples. The goethite-like form of hemosiderin that has been observed in some pathological tissues was not detected. © 1994 J.C. Baltzer AG, Science Publishers.